Regulating the Right to be Forgotten in Cyberspace: Heterogeneity of Loyalties within the Regulatory Environment - Melo, Jussara Costa (Law, State and Telecommunications Review, 2015)
Purpose ”“ This paper aims to enhance the comprehension of the diversification of public responsibility within the legislators’ intention on regulating the right of privacy and also the right to be forgotten in the Congress Proposal no. 7,881/2014 and PLS 181/2014. Methodology/approach/design ”“ The paper is adopts deductive reasoning and descriptive methodology combined with discourse analysis. It employs the general theory of the state as a framework to explain the state course of action towards the Regulatory State. Findings ”“ The study identifies the international and economic motivation for legislative proposals designed to meet the technological communication requirements in a new market in which data and information are owned by corporations. Practical implications ”“ The paper strengthens the thesis of diversification of public responsibilities and points to difficulties for the effectiveness of the regulatory proposals considering technical complexity and asymmetry between users and providers of research mechanisms on access and use of the contents stored in the virtual world. Originality/value ”“ The article is not original in its contents. Nevertheless it points contractual risks in the intense flow of exchanges in the Internet and throws light on the absence of a transnational State that could embody the overall protection of privacy and right to be forgotten against the power of large corporations.